A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mohammad, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)

A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Processes, 2023)
The aim of this study is to examine how CO2 gas hydrates (CO2 GH) are used in baking, notably in the creation of wheat bread, as a leavening agent. CO2 GH were produced with the use of food grade amino acids called promoters. The article emphasizes an interesting approach by using a hybrid combination of yeast and CO2 GH. The current study is based on a comparative evaluation of leavening agents in bread with (1) GH with promoters (20–70% GH) and (2) GH with promoters + yeast as a partial replacement (25–75%). The results obtained are then also compared with those of standard yeast bread along with the effects on wheat bread quality parameters such as volume, specific volume, hardness, moisture content, baking loss, and pore size. The GH bread with promoters had baking losses that were equivalent to the quality of traditional yeast bread. The breads with 60% and 70% GH with promoters had the best outcomes when compared with standard yeast bread. When a combination of CO2 GH with promoters (20–70%) and yeast (25–75%) was used in the study, the best combinations were obtained with 70% GH + 50% yeast and 70% GH + 75% yeast. Additionally, this article clarifies some potential future uses for CO2 GH as leavening agents in the bread industry, with a discussion of potential limitations as well as the cost efficiency of the developed technology. This information could help in the creation of new methods and standards for better CO2 GH selection for usage in other bakery goods.
CRIS-Team Scopus Importer:2023-04-14
Keywords: amino acids; bread; CO; leavening; promoters; yeast

A discrete element cohesive particle collision model for the prediction of ash-induced agglomeration - Gatternig, Bernhard; Karl, Jürgen (International Journal of Ambient Energy, 2019)
Keywords: Biomass combustion; ash agglomeration; fluidized bed combustion; discrete element method; particle modelling

An Innovative Approach in the Baking of Bread with CO2 Gas Hydrates as Leavening Agents - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Claßen, Timo; Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Foods, 2022)
Gas (guest) molecules are trapped in hydrogen-bonded water molecules to form gas hydrates (GH), non-stoichiometric solids that resemble ice. High pressure and low temperature are typical conditions for their development, with van der Waals forces joining the host and guest molecules. This article study investigates the application of CO2 gas hydrates (CO2 GH) as a leavening agent in baking, with particular reference to the production of wheat bread. The main intention of this study is to better understand the complex bread dough formed by CO2 GH and its impact on product quality. This may enable the adaptation of CO2 GH in baking applications, such as those that can specifically influence wheat bread properties, and so the final bread quality. The present research further examines the comparative evaluation of yeast bread with the GH bread’s impact on bread quality parameters. The amount of GH was varied from 10 to 60%/amount of flour for the GH breads. The GH breads were compared with the standard yeast bread for different quality parameters such as volume, texture, and pore analysis. The results show that the bread with 20% and 40% GH obtained the best results in terms of volume and pore size. Moreover, this article also sheds some light on the future applications of the use of CO2 GH as leavening agents in foods. This knowledge could help to create new procedures and criteria for improved GH selection for applications in bread making and other bakery or food products.
CRIS-Team Scopus Importer:2022-12-02
Keywords: bread; browning; CO; dough; food applications; leavening; leavening

Application of chemical equilibrium calculations for the prediction of ash-induced agglomeration - Gatternig, Bernhard; Karl, Jürgen (Biomass Conversion and Biorefinery, 2018)

Application of chemical equilibrium calculations for the prediction of ash-induced agglomeration - Gatternig, Bernhard; Karl, Jürgen (Biomass Conversion and Biorefinery, 2019)

Application of CO2 Gas Hydrates as Leavening Agents in Black-and-White Cookies - Kollemparembil, Ann Mary; Srivastava, Shubhangi; Zettel, Viktoria; Gatternig, Bernhard; Delgado, Antonio; Jekle, Mario; Hitzmann, Bernd (Foods, 2023)
In this unprecedented study, the application of CO2 gas hydrates (GH) as a leavening agent to produce black-and-white cookies by replacing ammonium bicarbonate is investigated. Ammonium bicarbonate, the principal leavening ingredient in black-and-white cookies, has been linked to the creation of a carcinogenic substance known as acrylamide. Three distinct GH concentrations, 20%, 40%, and 50%, were utilized to determine the necessary amount to obtain a good leavening effect. However, the abrupt reduction in temperature brought on by the addition of GH had an inadmissible effect on the cookie dough. Consequently, an innovative kneading method carried out in a closed mixing unit at a high temperature was developed. The specific volume of the cookies when employing 50% GH as a baking agent was more than half that produced when using ammonium bicarbonate. In the cookies with GH, the springiness and hardness, which are the quality-determining textural characteristics of the pastry, remained within an acceptable range. The amount of acrylamide was reduced from 24.8 µg/Kg to around 18 µg/Kg by this research. Therefore, the presented study demonstrates the possibility of using CO2 GH as a leavening agent in black-and-white cookies and in other products for a healthier future.
CRIS-Team Scopus Importer:2023-08-11
Keywords: acrylamide; ammonium bicarbonate; baking; black-and-white cookie; gas hydrate; leavening agent

A Scientific Adventure. Testing a F.A.N. Theory - Dreyer, Boris; Gatternig, Bernhard (Ancient Warfare, 2019)
Keywords: Kelten Römer; Warship; F.A.N.

CO2 gas hydrate as an innovative leavening agent for baked goods - Frühling, Yvonne; Claßen, Timo; Mobarak, Mohammad Mobarak; Bauer, Marius; Zettel, Viktoria; Gatternig, Bernhard; Hitzmann, Bernd; Delgado, Antonio (Future Foods, 2023)
In the presented research, the use and technical realization of CO2 gas hydrate (GH) as a novel baking agent is investigated. GH are ice-like structures where one mole of hydrate typically consists of about 85% water and 15% gas. Hydrates were formed in a lab-scale 1.1 L stirred tank reactor at 1-2 degrees C and 3.5 MPa, and transferred into a temperature-controlled, gas-tight measuring cell. The leavening effect of gas hydrates was assessed by measuring the CO2 release rates. Storage stability at-20 to 0 degrees C and stability above 0 degrees C were investigated experimentally and a coupled thermodynamic and kinetic decay model implemented. At-10 degrees C, gas release was highest in the first minutes and stopped completely after 5 days. After 21 days storage at-10 degrees C, the GH still contained 20 % of the initial gas content. Above 0 degrees C, dissociation rates were highly temperature dependent, and half value times ranged from 30 min (3 degrees C) to 4 min (20 -30 degrees C). Above 10 degrees C, ambient temperature had only a minor effect on the dissociation rates. Results from the kinetic decay model, applied for a 21 mm particle, showed similar dissociation behavior as a particle from experiments. Applying the model for a 3 mm particle, showed full dissociation after approximately 15 min. Stability and baking tests showed that CO2 hydrate is in principle suitable as a leavening agent. However, GH production still needs to be optimized and recipes for GH application require further development.
CRIS-Team WoS Importer:2023-04-14

Concentration of apple juice using CO(2 )gas hydrate technology to higher sugar contents - Claßen, Timo; Jäger, Michael; Loekman, Soebiakto; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Innovative Food Science & Emerging Technologies, 2020)
This paper describes the application of CO2-hydrate technology for the concentration of apple juice towards industrially relevant levels. Assays were carried out in a stirred autoclave at 1-2 degrees C and 35 bars with rediluted apple concentrate in the range of 11 degrees Bx to 40 degrees Bx. A hydraulic pellet press was used to separate the hydrate from the concentrate, resulting in an almost complete sugar recovery. It was found that apple juice can be concentrated to 45 degrees Bx and beyond using this technique. Maximum hydrate conversion of up to 30% was achieved at an average concentration rate of 2.5-3 degrees Bx/h. Furthermore, an optimal juice to crystallizer volume ratio of 35% was found. The investigations also revealed the juice composition to interfere with the hydrate formation process to some extend. In the assays with constant water content, no decrease in the hydrate formation rate was observed until 30 degrees Bx. From this concentration onwards, however, the hydrate yield decreased steadily and amounted to only 15% M 40 degrees Bx.
CRIS-Team WoS Importer:2020-09-25

Development of an explicit pressure explicit saturation (EPES) method for modelling dissociation processes of methane hydrate - Luzi, Giovanni; Prah, Benedict; Loekman, Soebiakto; Gatternig, Bernhard; Delgado, Antonio (High Pressure Research, 2022)
Methane gas is a fossil clean fuel since the products of the combustion are only carbon hydrate and water. Methane hydrate is a potential source of methane gas. This ice-like methane source can be found in deep seafloors and permafrost regions, characterized by high pressure and low-temperature conditions. In this work, we simulate the process of methane hydrate dissociation by depressurization in a cylindrical sandstone core by means of a two-dimensional axis-symmetric model, focusing on the transport phenomena involved in the process. Our simulations indicate a first rapid dissociation phase due to depressurization itself, and a longer subsequent one due to the thermal exchange with the external environment. Our numerical results match well with experimental data found in the literature, without showing any significant pressure or temperature delay among different sections compared to other numerical studies.
CRIS-Team WoS Importer:2023-01-13

Development of novel modelling approaches for agglomeration prediction - Gatternig, Bernhard; Karl, Jürgen (21st Euorpean Biomass Conference and Exhibition, 2013)

Die F.A.N. virtuell besuchen und testen: Graphische Datenverarbeitung, Numerik und das Römerboot - Stamminger, Marc; Rückert, Darius; Dreyer, Boris; Gatternig, Bernhard (Die Fridericiana Alexandrina Navis (F.A.N.). Ein Römerboot auf dem Prüfstand – Bau und Test für Wissenschaft und Öffentlichkeit, 2022)
Keywords: Antike; Römische Kaiserzeit; Experimentelle Archäologie; Schifffahrt; Interdisziplinär; Graphische Datenverarbeitung

Einfluss von Hochleistungs-Ultraschall auf Getränkeschäume - Delgado, Antonio; Thünnesen, Julian; Gatternig, Bernhard (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
In der Getränkeindustrie kommt es bisweilen zur ungewünschten Schaumbildung während der Flaschenabfüllung von Säften, die zur Verringerung der Abfüllgeschwindigkeit und Dosiergenauigkeit führen. Um die Schaumbildung zu verringern, erweist sich Ultraschall als eine effektive Methode (Gallego-Juárez et al., 2015). Es wird vermutet, dass der Ultraschall Oberflächenwellen auf den Flüssigkeiten erzeugt, die Drainage im Schaum erhöht und den Schaum dadurch destabilisiert (Sandor und Stein, 1993; Morey et al., 1999). Hinzu kommen noch frequenzabhängige Eigenresonanzeffekte der Schaumblasen, wurden bereits in einer früheren Arbeit beobachtet, die sich der Optimierung von Sacklöchern in Mikrometerbereich widmete (Vaidya et al., 2016). Sie wurden aber im Hinblick auf einen forcierten Schaumzerfall bislang noch nicht betrachtet. Thema des Beitrags ist die Betrachtung des Schaumzerfalls unter dem Einfluss von Ultraschall unterschiedlicher Frequenzen. Es werden Ergebnisse von Versuchen vorgestellt, bei denen Schäume von Säften mit unterschiedlichen Ultraschallfrequenzen (35-120 kHz) zum Zerfall gebracht wurden. Neben der Erfassung der verringerten Schaumhöhe, nahm eine Hochgeschwindigkeitskamera (Fa. Shimadzu, 1 Mfps) die Lamellenvibrationen während der Beschallung auf. Es wurde ersichtlich, dass frequenzabhängig unterschiedliche Blasengrößen resonierten und kollabierten, der Tröpfchenauswurf aus den Lamellen verändert wurd
Keywords: Ultraschall; Entschäumung; Fruchtsäfte

Entwicklung eines auf Referenz-Petri-Netzen basierenden hybriden Simulationstools zur wissensbasierten Reduzierung des Energie- und Wasserbedarfs bei der Weinerzeugung - Schütz, Martin; Schwinn, Mira; Hussein, Mohamed; Gatternig, Bernhard; Groß, Frauke; Durner, Dominik; Fischer, Ulrich; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
The objective of the research presented here was the development of a Reference-Petri Net-work-based hybrid simulation tool for the knowledge-based reduction of energy and water re-quirements in wine production. Data surveys on the water and electrical energy requirements, based on 1000 liters of the finished product, reveal deviations that in some cases significantly exceed the factor of 10. Using the developed simulation tool, winemaking processes in indi-vidual companies can be simulated and analysed for weak points. The hybrid tool uses Refer-ence-Petri-Nets as a structuring element. A developed basic structure enables the creation of a "virtual twin" of existing wine businesses as well as various calculations and output options for the individual processes by the user. Comparisons of different actions and expenditure of savings potential bring a new transparency into the overall process chain of winemakin
Keywords: Prozessvirtualisierung; Modellierung und Simulation; Energiemanagement; Referenznetze

Experimental investigation of CO2 uptake in CO2 hydrates formation with amino acids as kinetic promoters and its dissociation at high temperature - Srivastava, Shubhangi; Kollemparembil, Ann Mary; Zettel, Viktoria; Classen, Timo; Gatternig, Bernhard; Delgado, Antonio; Hitzmann, Bernd (Scientific Reports, 2022)
The dissociation of CO2 gas hydrates (GH) with amino acid kinetic promoters and without promoters was studied at a high temperature of 90 degrees C for a period of 20 min to understand the percentage of CO2 gas and to select the best promoter that aids CO2 gas entrapment along with stability at a high temperature. The possibility of using four hydrophobic food grade amino acids, namely cysteine, valine, leucine, and methionine, and one surfactant, lecithin, as kinetic promoters for CO2 GH has been studied. The amino acids were added 0.5 g (wt%), and lecithin was added 5 g for the GH production. Furthermore, the amino acids leucine and methionine gave some positive results, therefore, these amino acids were carried further for the experimentation purpose in the production of CO2 GH. Also, a combinational use of these amino acids was studied to investigate the effect on % CO2 retention in comparison to the normal GH. From the results, it was observed that the stability of GH decreases with an increase in temperature, but the addition of promoters, especially leucine + methionine + lecithin increased the CO2 uptake during GH formation.
CRIS-Team WoS Importer:2022-06-17

Foam Drainage Parametric Study Using the Lattice Boltzmann Method Considering the Non-Newtonian Behavior - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio; Bernstein, Thomas; Mchardy, Christopher; Rauh, Cornelia (Chemical Engineering & Technology, 2022)
Foam exists in several food and chemical processes. It often delays, contaminates, and obstructs the industrial process, which affects the product's quality and safety. Liquid drainage in foam is one of the most influencing physical phenomena impacting its behavior, and is characterized by its short time scales. The lattice Boltzmann method (LBM) is applied to develop a consistent method for evaluating the permeability of different foam structures, while considering the non-Newtonian behavior of its liquid lamella. Foam drainage for non-Newtonian fluids is not well understood and established in literature. Different geometrical and liquid parameters are thus considered and analyzed, in order to generate a map for the foam permeability.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Foam drainage; Foam structures; Lattice Boltzmann method; Non-Newtonian fluids

Foam dynamics in non-Newtonian fluids using Lattice Boltzmann Method and its application in food industry - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Hussein, Mohamed; Delgado, Antonio (ProcessNet 2019, 2019)

Food foams simulations by the means of multicomponent lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (9th European Postgraduate Fluid Dynamics Conference, 2019)

Heat transfer in deformable foams by the means of multicomponent Lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Hussein, Mohamed; Osorio Nesme, Anuhar; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Foam propagation is a complex and challenging topic in food and chemical industry. Foam exists in several industrial applications such as food supply and discharge pipes, dairy products tanks and rectification columns. Foams often influence the mass, momentum and energy transport as well as the biochemical reactions. Consequently, this leads to a significant additional consumption of time and energy, and also to a loss of product quality and safety. The proposed approach is to apply a multi-component Lattice Boltzmann method, namely Shan-Chen pseudopotential model coupled with thermal LBM in order to simulate the complex heat transfer process in foams, taking into account the foam dynamics and deformation. The approach is to use multi-distribution functions for the multicomponent flow and temperature fields considering the different physical parameters for each phenomenon. The Lattice Boltzmann Method (LBM) has recently gained great attention in thermal flow field modelling, especially in complex media. One great advantage of the method is that it handles complex geometries and obstacles in a simple manner. LBM also gained much attention and success in the field of multicomponent and multiphase flows, one benefit is that it does not need an explicit additional algorithm for interface tracking. These simulations will provide a deeper insight in the foam dynamics and heat transfer process inside this nonhomogeneous medium. This can provide the basis for a prediction tool that regards the foaming causes and effects in several industrial processes. Several Industrial sectors with various products like beverages and milk can benefit from this tool, as the foaming in beverages’ filling and dairy production can be controlled and optimized on this basis. Other applications are chemical production facilities that deal with columns and evaporators which also encounter critical foaming issue
Keywords: Lattice Boltzmann Method; Multiphase-Multicomponent flow; Shan-Chen Pseudopotential Model; Thermal Flows; Food Foams

Investigations on the mechanisms of ash-induced agglomeration in fluidized-bed combustion of biomass - Gatternig, Bernhard; Karl, Jürgen (Energy & Fuels, 2015)

Leistungsdiagnostik auf der Fridericiana Alexandrina Navis (F.A.N.) – eine Pilotstudie - Kemmler, Wolfgang; Dreyer, Boris; Gatternig, Bernhard (Die Fridericiana Alexandrina Navis (F.A.N.). Ein Römerboot auf dem Prüfstand – Bau und Test für Wissenschaft und Öffentlichkeit, 2022)
Keywords: Antike; Römische Kaiserzeit; Experimentelle Archäologie; Schifffahrt; Interdisziplinär; Leistungsdiagnostik; Pilotstudie

Modelling and simulation of food foams with different material consistencies - Mobarak, Mohammad Mobarak; Gladbach, Katharina; Chen, Nan; Gatternig, Bernhard; Osorio Nesme, Anuhar; Hussein, Mohamed; Delgado, Antonio (GDL – Symposium Lebensmittelschäume, 2019)

Neural network enhanced aging time measurements of diary product remaining with infrared spectroscopy - Beck, Tobias; Gatternig, Bernhard; Delgado, Antonio (Heliyon, 2023)
The determination of the drying degree of food residues on surfaces is an important step before efficient cleaning can be achieved. To accomplish this goal, a rapid evaluation based on a neural network and non-invasive measurement technique is introduced. Two common starch-based products and various yogurts from different manufacturers are used as example contaminants to determine the aging time of dried food residue. Near-infrared spectroscopy serves as a modern and fast measurement technique for investigating food compositions. Two analysis methods were compared for processing the measured near-infrared spectral data. The raw data were analyzed using partial least squares regression in conjunction with necessary preprocessing steps. As an alternative method, three different types of neural networks are employed. The aim of this approach is to compensate for the filtering steps before regression, which are typically necessary for multivariate regression. The challenge is to measure three different types of food and obtain a reliable prediction of moisture content in order to draw conclusions about the drying time. The experiments have shown that simple flat neural networks have similar accuracy compared to conventional regression. The use of a convolutional layer in advance demonstrates a significant improvement in prediction compared to other neural networks and even manages to surpass the accuracy of PLS regression. A network with a convolutional layer can also compensate for the sometimes strong variations between food types.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Food processing; Near infrared; Neural network

On the Simulations of Thermal Liquid Foams Using Lattice Boltzmann Method - Mobarak, Mohammad Mobarak; Gatternig, Bernhard; Delgado, Antonio (Energies, 2023)
Liquid foams exist in a wide variety of chemical and industrial processes, and they can contaminate the end-product and cause time and economical losses. Understanding and simulating foam is not a straightforward task, due to the highly dispersed time and length scales where the physical phenomena occur. Surfactants’ or proteins’ length scales are far beyond the capability of macroscopic and even mesoscopic numerical fluid solvers, yet the macroscales are still required to be resolved. Meanwhile, the lattice Boltzmann method (LBM) has gained much attention and success as a mesoscopic approach which can deal with complex multiphase multicomponent systems. The aim of this study is to implement LBM to simulate liquid foams while considering the accompanying thermal effects. A coupled multiphase multicomponent thermal flow model and its selected add-ons from the literature are tuned and explained, limitations and future suggestions are fairly discussed. Validations and a final study case are shown as an example for the proposed model and its applicability in thermal liquid foams. Finally, a delicate treatment to back couple the effect of temperature on the surface tension is proposed, hence considering one aspect of the Marangoni effect. Initial results show promising behavior, which can be material for future investigations.
Created from Fastlane, Scopus look-up
Keywords: heat transfer; lattice Boltzmann method; liquid foam; multiphase multicomponent flows

Phenomena, mechanisms and structures in wished and unwished foams in matter of biological origin - Gatternig, Bernhard; Osorio Nesme, Anuhar; Almazan Torres, Lidia; Thünnesen, Julian; Beck, Tobias; McHardy, Christopher; Bernstein, Thomas; Luzi, Giovanni; Stahl, Thomas; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy ANBRE19, 2019)

Potential Application of Innovative Gas Hydrate Technology in Fruit Juices Concentration Process - Loekman, Soebiakto; Claßen, Timo; Seidl, Pia; Luzi, Giovanni; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy, 2019)

Prediction of ash-induced agglomeration in biomass-fired fluidized beds by an advanced regression-based approach - Gatternig, Bernhard; Karl, Jürgen (Fuel, 2015)
Keywords: Ash agglomeration; Fluidized bed combustion; High ash biomass fuels; Predictive modeling

Resonant Ultrasonic Defoaming in Aqueous Evaporation/Boiling Processes at Different Size Scales - Thünnesen, Julian; Gerstenberg, Christoph; Heller, Daniel; Leuner, Hannes; Einfalt, Daniel; Mchardy, Christopher; Gatternig, Bernhard; Rauh, Cornelia; Repke, Jens-Uwe; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foam bears the risk of affecting different thermal industrial processes negatively, by reduced process efficiency, contamination, and total shutdown. Mechanical defoaming methods are difficult to implement, while chemical anti-foaming agents are challenging in correct dosing. Ultrasonic defoaming actuators destroy foams purely mechanically from air-borne, but their energy consumption per area is still excessive at 10 W cm(-2). Results show that a frequency sweep between 40-168 kHz and a water-borne sonication needs power densities of around 0.1 W cm(-2) for a lab-scale experiment to a copper column still. At this power level, ultrasound enforces the foam drainage, thus reducing the foam height and the process time of the column still by 20 %. The chosen frequency range indicates a resonant behavior of small liquid-loaded lamella and plateau channels.
CRIS-Team WoS Importer:2022-06-03

Review on the food technological potentials of gas hydrate technology - Claßen, Timo; Seidl, Pia; Loekman, Soebiakto; Rauh, Cornelia; Delgado, Antonio; Gatternig, Bernhard (Current Opinion in Food Science, 2019)
Gas hydrate technology has been known for a long time, but has only recently gained interest in food technology field. A major advantage for food technology applications are the gentle conditions under which products can be refined using gas hydrates, therefor not altering or damaging valuable product contents. This review discusses recent developments of hydrate applications for different areas of food technology for example concentration and purification processes, the preservation of foodstuff as well as novel product designs.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Gashydrate; Lebensmitteltechnologie; Fruchsaftkonzentration

Schaum- und Füllstanderkennung mittels optischer System mit neuronalen Algorithmen - Beck, Tobias; Gatternig, Bernhard; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)

Strömungsmechanische Tauglichkeitsanalyse der Fridericiana Alexandrina Navis (F.A.N.) - Thünnesen, Julian; Günther, Hans Moritz; Wawrzyn, Alexander Christopher; Dreyer, Boris; Gatternig, Bernhard (Die Fridericiana Alexandrina Navis (F.A.N.). Ein Römerboot auf dem Prüfstand – Bau und Test für Wissenschaft und Öffentlichkeit, 2022)
Keywords: Antike; Römische Kaiserzeit; Experimentelle Archäologie; Schifffahrt; Interdisziplinär; Strömungsmechanik

The Influence of Particle Size, Fluidization Velocity, and Fuel Type on Ash-Induced Agglomeration in Biomass Combustion - Gatternig, Bernhard; Karl, Jürgen (Frontiers in Energy Research, 2014)

Ultrasonic Effects on Foam Formation of Fruit Juices during Bottling - Thünnesen, Julian; Gatternig, Bernhard; Delgado, Antonio (Eng, 2021)
Non-carbonated fruit juices often tend to foam over during bottling. The resulting foam height corresponds to the equilibrium of foam formation and decay. Therefore, the foam unexpectedly occupies more space in the bottle and carries parts of the juice out of the bottle, resulting in product loss under filled containers and hygienic problems in the plant. Chemical antifoams are likewise undesirable in most cases. Recent ultrasonic defoamers are effective but only capable outside the container and after the filling. In this article, a lateral ultrasonication through the bottle wall with frequencies between 42 and 168 kHz is used in-line for non-invasive foam prevention during filling. Foam formation during hot bottling of orange juice, apple juice, and currant nectar at 70 °C happens at flow rates between 124–148 mL/s. The comparably high frequencies have a particular influence on the fresh foams, where a large fraction of small resonant bubbles is still present. Foam volume reductions of up to 50% are reached in these experiments. A low power of 15 W was sufficient for changing the rise of entrained bubbles and minimizing the foam development from the start. The half-life of the remaining foam could be reduced by up to 45% from the reference case. The main observed effects were a changed rise of entrained bubbles and an increased drainage.
CRIS-Team Scopus Importer:2024-12-16
Keywords: foam drainage; foaming behavior; fruit juice; glass bottles; ultrasound application